2016
DOI: 10.1007/s10157-016-1312-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between medication adherence and clinical outcomes in patients with chronic kidney disease: a prospective cohort study

Abstract: The findings suggest that CKD patients with poor medication adherence are more likely to have progression of CKD. Health care providers should acknowledge these findings and provide effective strategies to deal with this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 22 publications
1
32
0
1
Order By: Relevance
“… 26 In contrast, a recent study that included 332 Stage 3 to 4 CKD patients in Thailand found that low adherence was associated with increased risk for CKD progression. 27 Our results reinforce the findings of this study in a larger diverse U.S. cohort.…”
Section: Discussionsupporting
confidence: 90%
“… 26 In contrast, a recent study that included 332 Stage 3 to 4 CKD patients in Thailand found that low adherence was associated with increased risk for CKD progression. 27 Our results reinforce the findings of this study in a larger diverse U.S. cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Medication nonadherence is common among kidney-transplanted adolescents, estimated at 43% in a systematic review (5). Adults with CKD and poor adherence are more likely to have progressive disease (6), graft loss, and death (7). Young adults are the highest risk age-group for kidney transplant loss (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…2011; Levey & Coresh 2012; Tangkiatkumjai et al . 2017), and patients with advanced CKD must adhere to fluid and diet restrictions as well as renal replacement therapy to optimise their health (Levey et al . 2009).…”
Section: Introductionmentioning
confidence: 99%